Factors influencing teachers’ attitudes to online teaching - YAMANI, Dalila (Journal of Human Sciences, 2023)
Teachers’ disaffection with online teaching is well known in universities around the world. This study sheds light on the factors that may cause this phenomenon. Basing on the Davis acceptance technology model, we conducted a study by questionnaire with a group of teachers at the university who carried out an online teaching experience, where we measured their attitudes towards this type of teaching before and after the experience. Despite the technical training the teachers received at the beginning, the findings showed that the teachers’ rate who perceived difficulties in online teaching increased significantly after the experience, and a negative attitude was developed among most of the teachers. A strong dependency relationship, statistically significant, was identified between this negative attitude and the difficulties of a pedagogical nature encountered by teachers.